Efektivitas Media E-Learning pada Pembelajaran Pendidikan Agama Islam (PAI) di Universitas Islam Negeri Raden Fatah Palembang - Al Ihwanah; Elhefni Elhefni (Indonesian Journal of Islamic Education Studies (IJIES), 2021)
The effectiveness of Islamic religious education (PAI) learning will be realized by the existence of tools that make it easier for students, please students, and can achieve lecture outcomes as they should. Utilization of learning media is an effort to improve the quality of lecture activities. If the quality of learning increases, the quality of student learning outcomes also increases. E-learning media help lecturers as a means of transferring knowledge and transferring values ​​according to lecture achievements. Based on the test results of the experimental class and the test results of the control class, data is obtained that there is a difference in the average increase in test scores between each class, where the average test score of the experimental class is higher than the control class. Thus, this e-learning media is effective in PAI learning. The use of e-learning media in the PAI learning process can improve the quality of lectures. E-learning media has various features and advantages that play a role in delivering innovative learning messages so that students are motivated in lecture activities. In addition, the learning materials in it can be delivered more effectively and efficiently, either typed directly or linked to other online media links.